World-renowned Linguist and Author, David Nunan with Pertanika JSSH - Universiti Putra Malaysia, Bahagian Komunikasi Korporat (2009)
SERDANG, 19 Nov - Pertanika Journal of Social Sciences and Humanities (JSSH) now has David Nunan on its Editorial Advisory Board.